MIDDLE RANGE THEORIES CHERYL TATANO BACK POST PARTUM DEPRESSION THEORY - Suci Rahmadia; Irna Nursanti (Yayasan Nusantara Hasana Berdikari, 2024)
Quality nursing services are supported by the development of nursing conceptual model theory. Professional nursing services will develop if they are supported by conceptual models and research and implemented in nursing practice. The nursing profession recognizes four levels of theory, namely meta-theory, middle theory, and practice theory. The nursing conceptual model was developed by experts as a framework for nursing thinking, so nurses need to understand this concept as a conceptual framework for thinking about providing nursing care in nursing practice. One of the middle-range theories that support the development of nursing in the development of science and in nursing practice was developed by Cheryl Tatano Back. Postpartum depression (PPD) is a major mental health disorder that affects at least 13 percent of new mothers and has detrimental consequences for populations of concern to social workers, such as low-income women, women of color, young women, and single mothers.